ETHICAL ORGANIZATIONAL CULTURE AND PERSON-ORGANIZATION FIT - Inkeri, Sanna (My University, 2012)
Ethicality has increased its importance in organizations as companies are expected to have social responsibility and to provide guidelines for employees about the ethicality inside the organizations. New laws are also pushing companies towards a more ethical organizational culture. Having a greater person-organization (P-O) fit can increase job satisfaction and it is easier for companies to implement their ethical organizational culture for the employees. The goal of this study is to focus on a single organization and to study their ethical organizational culture through Corporate Ethical Virtues (CEV) –model and to further analyze the P-O fit using the same CEV –model. Finally to see whether the greater P-O fit increases job satisfaction. The results supported earlier studies in the fields of ethical organizational culture studies and the studies generated of P-O fit. Although this study produced new results through the choice of the organization and through combining the studies of CEV and P-O fit. Data was collected though an online questionnaire using the e-lomake browser based application. The response rate was 49.2 %. The ethicality of the organization was generally estimated rather high by the employees. Also the person-organization fit was assessed as quite high. Clarity reached the highest scores out of the eight ethical virtues. This describes the organization as being a place where the ethical norms and values are clearly presented and they are also understood by the employees. Also congruency of supervisors and management reached high scores which is defined as the actions of both supervisors and management level are reflecting the organization’s rules, norms and expectations. This study also confirms the findings of previous studies and found a connection between P-O fit and higher job satisfaction while pointing out that job satisfaction is reached through many different dimensions.
Keywords: Organizational culture; virtues; ethical organizational culture; person-organization fit; job satisfaction; fi=Master's Degree Programme in International Business|